Pengembangan Sistem Deteksi Otomatis untuk Kelayakan Lingkungan Penanaman Microgreen Buatan Berbasis Sensor IoT - Sari, Eka Yulia; Rahmawati, Titik; Septianto, Yudhistira Wahyu; Maharani, Rahil Putri (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2024)
One of the issues that needs to be acknowledged by all parties is the decreasing agricultural land due to its conversion into residential areas, while the human population continues to grow in proportion to food demand. Urban farming emerges as a solution to address the constraints of agricultural land by utilizing available space. Moreover, urban farming could be the support for food security, especially at the household level. The utilization of IoT technology could be applied to support this urban farming initiative. We have designed a prototype of an artificial ricefield for microgreen cultivation that is integrated with IoT to monitor the planting process and provide environmental feasibility recommendations. Environmental feasibility recommendations are measured by three indicators: room temperature, air humidity, and soil moisture. The devices used are the DHT11 sensor for detecting temperature and air humidity, and the NodeMCU ESP32 DevKit V.1 microcontroller for data processing, enabling the DHT11 sensor detections to be displayed on a website. The test results show that the Mean Squared Error (MSE) for each indicator is as follows: temperature 2,9 %, air humidity 3,9 %, and soil moisture 5,4%. Because each indicator of the MSE value obtained is low, this prototype is suitable for development.